Phytomanagement and Remediation of Cu-Contaminated Soils by High Yielding Crops at a Former Wood Preservation Site: Sunflower Biomass and Ionome - Mench, Michel J.; Dellise, Marie; Bes, Clémence M.; Marchand, Lilian; Kolbas, Aliaksandr; Le Coustumer, Philippe; Oustrière, Nadège (Frontiers in Ecology and Evolution, 2018)
This long-term trial aimed at remediating the biomass production and other soil functions at a former wood preservation site. 28 field plots with total topsoil Cu in the 198 - 1169 mg kg-1 range were assessed. 24 plots (OMDL) were amended in 2008 with a compost (made of pine bark chips and poultry manure, OM, 5% w/w) and dolomitic limestone (DL, 0.2%), and thereafter annually phytomanaged with a sunflower – tobacco crop rotation; in 2013, one untreated plot (UNT) was amended with a green waste compost (GW, 5%) whereas 12 former OMDL plots received a second compost dressing using this green waste compost (OM2DL, 5%). In 2011, one plot was amended with the Carmeuse basic slag (CAR, 1%) and another plot with a P-spiked Linz-Donawitz basic slag (PLD, 1%). Thus six soil treatments, i.e. UNT, OMDL, OM2DL, GW, CAR and PLD, were cultivated in 2016 with sunflower (Helianthus annuus L. cv Ethic). Shoots were harvested, wet-digested and their ionome analysed. Soil texture and physico-chemical parameters were determined in all plots. All amendments improved the soil nutrient status and the soil pH, which was slightly acidic in the UNT soil. Total organic C and N and extractable P contents peaked in the OM2DL soils. Both OMDL and OM2DL treatments led to higher shoot DW yields and Cu removals than the GW, CAR and PLD treatments. Shoot DW yields decreased as total topsoil Cu rose in the OMDL plots, on the contrary to the OM2DL plots, demonstrating the benefits to repeat compost application after five years. Shoot Cu concentrations notably of OMDL and OM2DL plants fitted into their common range and can be used by biomass processing technologies and oilseeds as well. In overall, there is a net gain in soil physico-chemical parameters and underlying soil functions.